A Case for the Non-Neurologist Telestroke Provider - Choi, Justin; Petrone, Ashley; Adcock, Amelia (Frontiers in Neurology, 2021)
Introduction: Telestroke networks have effectively increased the number of ischemic stroke patients who have access to acute stroke therapy. However, the availability of a dedicated group of stroke subspecialists is not always feasible. We hypothesize that rates of tPA recommendation, sensitivity of final diagnosis, and post-tPA hemorrhagic complications do not differ significantly between neurologists and an emergency-medicine physician during telestroke consultations. Methods: Retrospective review of all telestroke consults performed at a comprehensive stroke center over 1 year. Statistical analysis: Chi squared test. Results: Three hundred and three consults were performed among 6 spoke sites. 16% (48/303) were completed by the emergency medicine physician; 25% (76/303) were performed by non-stroke-trained neurologists, and 59% (179/303) were completed by a board-certified Vascular Neurologist. Overall rate of tPA recommendation was 40% (104/255), 38% (18/48), 41% (73/179), and 41% (31/76) among the all neurology-trained, emergency medicine-trained, stroke neurology-trained and other neurology- trained provider groups, respectively (p = 0.427). Sensitivity of final stroke diagnosis was 77% (14/18) and 72% (75/104) in the emergency-medicine trained and neurology-trained provider groups (p = 0.777) No symptomatic hemorrhagic complications following the administration of tPA via telestroke consultation occurred in any group over this time period. One asymptomatic intracerebral hemorrhage was observed (0.96% or 1/104) in the neurology-trained provider group. Discussion/Conclusion: Our results did not illustrate any statistically significant difference between care provided by an emergency medicine-trained physician and neurologists during telestroke consultation. While our study is limited by its relatively low numbers, it suggests that identifying a non-neurologist provider who has requisite clinical experience with acute stroke patients can safely and appropriately provide telestroke consultation. The lack of formerly trained neurologists, therefore, may not need to serve as an impediment to building an effective telestroke network. Future efforts should be focused on illuminating all strategies that facilitate sustainable telestroke implementation.